Aggregate gradation effect on the mechanical properties of asphalt mixtures - Imad Dawood, Sulaiman; M abed, Jasim; Zaid Hazim, Al-Saffar; Putra Jaya, Ramadhansyah (IOP Science, 2024)
, ,The issue of road deterioration in Mosul, Iraq, has become a matter of concern for local communities. The instability of road surfaces under the stress of vehicular traffic necessitates significant intervention to mitigate and manage this problem. This study has developed an asphalt mixture by following the Bailey method for aggregate gradation. The impact of aggregate gradation on the mechanical properties of the asphalt mixture was thoroughly analysed. Additionally, two separate mixtures were conducted using the conventional Marshall method to assess indirect tensile strength, Marshall properties, and susceptibility to moisture damage. The primary objective of this research is to design an aggregate structure that acts as a robust unit capable of withstanding heavy loads, repeated stresses, and high temperatures. The findings of the study indicate that the asphalt mixture created using the Bailey method exhibited superior stability with values of 13.6 kN, compared to the two traditional mixtures (11.8 kN, 9.2 kN), and. However, it is worth noting that the flow values also indicated a relative preference for the Bailey method, with values of and 3.1 mm, compared with 3.85 mm and 3.2 mm of the traditional mixtures. The results of Tensile strength ratio further corroborated the efficacy of Bailey's technique, with outcomes of 85.1 %, thus enhancing the applicability of this method. This observation is attributed to the concept of granular interlocking, which forms the foundation of the Bailey method.